2019
DOI: 10.1093/mutage/gez041
|View full text |Cite
|
Sign up to set email alerts
|

The activating transcription factor 2: an influencer of cancer progression

Abstract: In contrast to the continuous increase in survival rates for many cancer entities, colorectal cancer (CRC) and pancreatic cancer are predicted to be ranked among the top 3 cancer-related deaths in the European Union by 2025. Especially, fighting metastasis still constitutes an obstacle to be overcome in CRC and pancreatic cancer. As described by Fearon and Vogelstein, the development of CRC is based on sequential mutations leading to the activation of proto-oncogenes and the inactivation of tumour suppressor g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 170 publications
1
39
0
Order By: Relevance
“…The MAPK14-ATF2-axis was functionally shown to represent a collateral pathway ensuring persisting ERK-activation in the presence of sorafenib-mediated RAF-inhibition, thereby driving drug resistance [ 11 ]. Therefore, combined de-repression of both MAPK14 and ATF2 as mediated by loss of miR-622 could mechanistically contribute to stronger activation of the beneficial MAPK14-ATF2-axis as compared with alternative pathways of ATF2-activation: ATF2 consists of multiple domains; the most prominent are the N-terminally located transactivation domain, the zinc finger, the bZIP domain and the nuclear localization and nuclear export signals [ 40 ]. Likewise, ATF2 can be phosphorylated by numerous kinases including MAPK14, ERK, PKC, JNK and also by ATM at different sites.…”
Section: Discussionmentioning
confidence: 99%
“…The MAPK14-ATF2-axis was functionally shown to represent a collateral pathway ensuring persisting ERK-activation in the presence of sorafenib-mediated RAF-inhibition, thereby driving drug resistance [ 11 ]. Therefore, combined de-repression of both MAPK14 and ATF2 as mediated by loss of miR-622 could mechanistically contribute to stronger activation of the beneficial MAPK14-ATF2-axis as compared with alternative pathways of ATF2-activation: ATF2 consists of multiple domains; the most prominent are the N-terminally located transactivation domain, the zinc finger, the bZIP domain and the nuclear localization and nuclear export signals [ 40 ]. Likewise, ATF2 can be phosphorylated by numerous kinases including MAPK14, ERK, PKC, JNK and also by ATM at different sites.…”
Section: Discussionmentioning
confidence: 99%
“…ATF2 is a member of the activator protein 1 (AP-1) TF family of the basic leucine zipper (bZIP)-containing DNA-binding proteins and plays crucial roles in cellular development and survival. 43 As a TF, ATF2 regulates miR-132 and miR-320a transcription by binding to their promoters. 44 , 45 However, it has not been reported whether ATF2 can activate lncRNA transcription by binding to the lncRNA promoter.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that ATF2 acts as an oncogene via promoting target genes transcription in many cancers [ 5 ]. Moreover, ATF2 is reported to be involved in the crosstalk between paraspeckles and mitochondrial signaling [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…ATF2 is activated by JNK, p38 (MAPK14) and ERK1 through Thr69 and Thr71-phosphorylation, then translocates into the nucleus and thus activates target genes transcription [ 4 ]. The activation of ATF2 promotes the expression of a series of target genes, which refer to cell cycle, immune and inflammatory responses and apoptosis regulation [ 5 ]. However, phosphorylated ATF2 at Thr52 by PKCε binds to the IFNβ1 promoter and represses gene transcription, indicating an transcription suppressor role of ATF2 [ 6 ].…”
Section: Introductionmentioning
confidence: 99%